UPAYA PELESTARIAN KESENIAN RANDAI MINANG SAIYO DI NAGARI LUBUK GADANG UTARA KECAMATAN SANGIR KABUPATEN SOLOK SELATAN - Yunita, Utri; Asriati, Afifah (Universitas Negeri Padang, 2026)
This research aims to reveal and describe the efforts to preserve Randai Minang Saiyo art in Nagari Lubuk Gadang Utara, Sangir District, South Solok Regency. This type of research is qualitative using a descriptive method. The research subject is the researcher themselves, assisted with writing tools and a camera. The types of data in this research are primary and secondary data. The data collection techniques in this research are literature study, observation, interviews, and documentation. The data analysis techniques in this research are data collection, data reduction, data presentation, and finally drawing conclusions.Research results show that efforts to preserve the Randai Minang Saiyo art are carried out through two aspects, namely the development of quantity and the usefulness of training outcomes used in art performances at Padang Aro Green Open Space. Quantity development is carried out by increasing the number of performers through regular training activities involving the younger generation and holding performances in art events at Padang Aro Green Open Space. Through this effort to increase performers, it has been proven capable of revitalising Randai activities and attracting public interest, especially among the younger generation.